2023
DOI: 10.1101/2023.01.19.524484
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automatic analysis of skull thickness, scalp-to-cortex distance and association with age and sex in cognitively normal elderly

Abstract: Transcranial brain stimulation has been a potential treatment for many brain diseases. The skull compartment exerts a strong influence on the delivery of stimulation, implying the need to accurately examine its geometry and alterations in the population. Here, we developed an open source efficient pipeline BrainCalculator based on BrainSuite Skullfinder for automatically computing the skull thickness map to locate the position of minimum thickness, scalp to cortex distance (SCD), and brain volume based on stru… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Skin colour varies widely across each racial category and throughout different seasons, emphasizing the importance of precise measurements rather than relying on broad racial categorizations. Moreover, we did not include sex-related or age-related differences, such as that in cranial thickness [46], into our modeling consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Skin colour varies widely across each racial category and throughout different seasons, emphasizing the importance of precise measurements rather than relying on broad racial categorizations. Moreover, we did not include sex-related or age-related differences, such as that in cranial thickness [46], into our modeling consideration.…”
Section: Discussionmentioning
confidence: 99%
“…The application of this specific imaging technology is more common in cases involving living. The representative studies [52,53,55] on skulls regarding sex estimation were based on living individuals' MRI images. Another non-invasive and non-radiation imaging technique that utilizes the soft tissue characteristic and applies to living individuals' sex estimation is ultrasound [68].…”
Section: Discussionmentioning
confidence: 99%
“…Head MRI was performed on healthy living individuals to estimate sex by measuring the width, height, and depth of the maxillary sinus; the results showed that males had a statistically significant difference in both the volume and dimensions of their maxillary sinus compared to females and the left maxillary sinus volume had the highest percentage of sexual dimorphism in the studied population [53]. Skull thickness and scalp-to-cortical distance measurements on MRI images from the open-source Alzheimer's Disease Neuroimaging-Initiative [54] were studied to estimate sex, the results suggested male participants tended to have thicker skulls than female participants, albeit this difference was not statistically significant [55]. To the author's best knowledge, the application of the MRI imaging method to sex estimation based on pelvic structure has not been reported.…”
Section: Mri and Sex Estimationmentioning
confidence: 99%